2014
DOI: 10.4132/koreanjpathol.2014.48.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protein Expression in Housekeeping Genes across Multiple Tissues in Rats

Abstract: BackgroundHousekeeping genes, which show constant protein expression patterns between different tissue types, are very important in molecular biological studies as an internal control for protein research.MethodsThe protein expression profiles of seven housekeeping genes (HPRT1, PPIA, GYS1, TBP, YWHAZ, GAPDH and ACTB) in various rat tissues (cerebrum, cerebellum, cardiac ventricle and atrium, psoas muscle, femoral muscle, liver, spleen, kidney, and aorta) were analyzed by Western blot and compared by coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…For detection of mRNA for metabolic genes commercially available TaqMan probes (Applied Biosystems, Waltham, Massachusetts, USA) dedicated to mouse tissue were used (see Supporting Information, Table S2). The level of mRNA for glycogen synthase ( Gys1 ) was used as reference (Kim et al, ). In contrast to Gys1 , our proteomic data revealed that the expression of all commonly used in qRT‐PCR referential genes (Boda, Pini, Hoxha, Parolisi, & Tempia, ) changed during aging or they were expressed at very low levels (Supporting Information, Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…For detection of mRNA for metabolic genes commercially available TaqMan probes (Applied Biosystems, Waltham, Massachusetts, USA) dedicated to mouse tissue were used (see Supporting Information, Table S2). The level of mRNA for glycogen synthase ( Gys1 ) was used as reference (Kim et al, ). In contrast to Gys1 , our proteomic data revealed that the expression of all commonly used in qRT‐PCR referential genes (Boda, Pini, Hoxha, Parolisi, & Tempia, ) changed during aging or they were expressed at very low levels (Supporting Information, Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…GAPDH was chosen to normalize vinculin quantity in the supernatant fraction (cytosol and membrane) across different samples because of its relatively high abundance and stable protein expression levels in tissues with different stiffness levels. [36] α-actin wasn’t used because of possible large variations in its protein expression levels over different stiffness. [36] Despite high Vcl levels at both 2 kPa and >GPa (polystyrene), vinculin protein expression level at 2 kPa in cytosol and membrane bound is significantly less than that from polystyrene (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…[36] α-actin wasn’t used because of possible large variations in its protein expression levels over different stiffness. [36] Despite high Vcl levels at both 2 kPa and >GPa (polystyrene), vinculin protein expression level at 2 kPa in cytosol and membrane bound is significantly less than that from polystyrene (Figure 2). Another interesting observation is that as stiffness increased up to 50 kPa, Vcl level decreased but vinculin protein expression increased.…”
Section: Resultsmentioning
confidence: 99%
“…However, the PCR efficiency can vary over time and across samples [49]. Therefore, the choice of an appropriate reference gene is fundamental to avoid an erroneous interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%